Columbia COVID‐19 Student Service Corps: Harnessing student skills and galvanizing the power of service learning. Issue 3 (30th December 2020) - Grilo, Stephanie A.; Catallozzi, Marina; Desai, Urmi; Sein, Aubrie Swan; Quinteros Baumgart, Cibel; Timmins, George; Edelman, David; Amiel, Jonathan M.
Abstract: The COVID‐19 pandemic in New York City led to the forced rapid transformation of the medical school curriculum as well as increased critical needs to the health system. In response, a group of faculty and student leaders at CUIMC developed the COVID‐19 Student Service Corps (Columbia CSSC). The CSSC is an interprofessional service‐learning organization that galvanizes the skills and expertise of faculty and students from over 12 schools and programs in the response to the COVID‐19 pandemic, and is agile enough to shift and respond to future public health and medical emergencies. Since March 2020, over 30 projects have been developed and implemented supporting needs identified by the health system, providers, faculty, staff, and students as well as the larger community. The development of the CSSC also provided critical virtual educational opportunities in the form of service learning for students who were unable to have any in‐person instruction. The CSSC model has been shared nationally and nine additional chapters have started at academic institutions across the country.